Involving patients in detecting quality gaps in a fragmented healthcare system: development of a questionnaire for Patients' Experiences Across Health Care Sectors (PEACS) - Noest, Stefan (Oxford University Press, 2014)
OBJECTIVE: The purpose of this study was to develop and validate a generic questionnaire to evaluate experiences and reported outcomes in patients who receive treatment across a range of healthcare sectors. DESIGN: Mixed-methods design including focus groups, pretests and field test. SETTING: The patient questionnaire was developed in the context of a nationwide program in Germany aimed at quality improvements across the healthcare sectors. PARTICIPANTS: For the field test, 589 questionnaires were distributed to patients via 47 general practices. MAIN MEASUREMENTS: Descriptive item analyzes non-responder analysis and factor analysis (PCA). Retest coefficients (r) calculated by correlation of sum scores of PCA factors. Quality gaps were assessed by the proportion of responders choosing a response category defined as indicating shortcomings in quality of care. RESULTS: The conceptual phase showed good content validity. Four hundred and seventy-four patients who received a range of treatment across a range of sectors were included (response rate: 80.5%). Data analysis confirmed the construct, oriented to the patient care journey with a focus on transitions between healthcare sectors. Quality gaps were assessed for the topics ‘Indication’, including shared-decision-making (6 items, 24.5–62.9%) and ‘Discharge and Transition’ (10 items; 20.7–48.2%). Retest coefficients ranged from r = 0.671 until r = 0.855 and indicated good reliability. Low ratios of item-non-response (0.8–9.3%) confirmed a high acceptance by patients. CONCLUSIONS: The number of patients with complex healthcare needs is increasing. Initiatives to expand quality assurance across organizational borders and healthcare sectors are therefore urgently needed. A validated questionnaire (called PEACS 1.0) is available to measure patients' experiences across healthcare sectors with a focus on quality improvement.